Cereal Coffee as a Functional Additive in Wheat Bread: Impact on Dough and Bread Properties - Grażyna Cacak-Pietrzak; Justyna Grabarczyk; Anna Szafrańska; Anna Krajewska; Dariusz Dziki (Foods)
The chemical composition and quality attributes of wheat bread enriched with cereal coffee were analyzed, with additive incorporated as a partial replacement for wheat flour at levels of 2%, 4%, 6%, 8%, and 10%. The rheological properties of the bread dough, consisting of wheat flour and cereal coffee blends, were evaluated using farinograph and extensograph analyses. Results indicated that the addition of cereal coffee decreased flour water absorption, extended dough stability, and increased dough softening. Dough containing cereal coffee showed greater resistance to stretching and reduced extensibility. However, the incorporation of cereal coffee led to a reduction in bread volume and an increase in crumb hardness and density, especially when the substitution level exceeded 6%. In terms of nutritional composition, the levels of dietary fiber, ash, fat, and total polyphenols increased with higher cereal coffee content, while crumb brightness decreased, and yellowness and redness intensified. Overall, the study suggests that cereal coffee can function as a valuable ingredient in bread; however, substitution levels should ideally be kept below 8% to preserve acceptable sensory qualities.